TRANCEDENTAL COMMUNICATION (A SOCIO PHENOMENOLOGY PERSPECTIVE) - Yunitasari, Yunitasari (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
Phenomenological       Sociology      einphazing      the     subjective      of·   exctsttng                                    g phenomena,  which isfrom  the seen socialfactthere   is something   urge individual                                    so to take action for  something   that  he believe. that  is right. The phenomena   doesnot refer lo  the society in general,  but refer to individual  which  sees human as agroup  of  individual   which   has  different   character   as-  well  as  has  differentperception,   attention.   also  interpretation.    For  example    the  movement   of  Al- Qiyadah Al-Islamiyah   and Ahmadiyah  Al-Qadiyan.